2018
DOI: 10.1186/s12888-018-1854-0
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with hospitalization after self-poisoning in France: special focus on the impact of alcohol use disorder

Abstract: BackgroundPrevious studies have identified factors associated with admission to hospital after suicide spectrum behaviors. In this study, we aim to identify specific factors associated with psychiatric hospitalization after self-poisoning. Given earlier findings suggesting that alcohol use disorder is not associated with hospital admission, we also aim to consider its impact, as well as blood alcohol concentrations, on hospitalization decisions after a suicide attempt.MethodsWe studied the association between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
7
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 49 publications
4
7
2
1
Order By: Relevance
“…Salles et al reported that an alcohol use disorder was unassociated with hospitalization for inpatient in psychiatric care, whereas depression clearly was an associated factor [20]. This study showed that alcohol use was unassociated with hospitalization; rather, alcohol use was higher in the discharge group.…”
Section: Discussionmentioning
confidence: 52%
“…Salles et al reported that an alcohol use disorder was unassociated with hospitalization for inpatient in psychiatric care, whereas depression clearly was an associated factor [20]. This study showed that alcohol use was unassociated with hospitalization; rather, alcohol use was higher in the discharge group.…”
Section: Discussionmentioning
confidence: 52%
“…Studies have shown associations between alcohol use disorder and suicidal behaviour [ 32 , 33 ]. Salles et al reported that an alcohol use disorder was not associated with hospitalisation for inpatient psychiatric care, whereas depression was a clearly associated factor [ 34 ]. This present study also showed that alcohol use was not associated with hospitalisation; rather, alcohol use before suicidal behavior was higher in the discharged group.…”
Section: Discussionmentioning
confidence: 99%
“…Among patients who visited the hospital after a suicide attempt, 80% received emergency hospitalization. In addition, all patients admitted for suicide attempts in France receive psychiatric assessments [4]. These assessments provide an opportunity to evaluate the suicide attempt, initiate treatment, and prevent future self-harm.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, these factors include violent or pre-planned suicide attempts, precautions to avoid rescue, increased mental suffering, regret over survival, limited social support, impulsive actions, and clear rejection of help. Hospitalization in departments other than the psychiatric ward is recommended when there is a change in level of consciousness due to metabolic, toxic, infectious, or other causes [4].…”
Section: Introductionmentioning
confidence: 99%